On the Theory of the Atrophy of the State: Questions of Methodology - Gasiūnas, A. (Problemos, 1979)
From the point of view of Marxist methodology of social theory, the state is an external manifestation of economic relations objectively preconditioned by class society. Therefore the atrophy of the state is an objective development related with the extermination of legislative confirmation of these economic relations. The opposing of the Marxist conception of the atrophy of the State and actual experience of socialism is typical of anti-Marxist and revisionist theories. This approach is based on idealist methodology of social theory.